2021
DOI: 10.1007/s11356-021-16104-6
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the therapeutic potential of marine-derived bioactive compounds against COVID-19

Abstract: The ocean is the most biodiverse habitat of various organisms. The organisms surviving in the harsh conditions of the ocean consist of several spectacular properties and produce bioactive compounds of pharmacological importance. These compounds are effective even in small quantities with various immunomodulatory qualities such as antioxidant and anti-inflammatory properties. Though the vaccines for COVID-19 are developed, and drug development is also in progress, but till now no effective drug is available for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 129 publications
(46 reference statements)
0
10
0
Order By: Relevance
“…Galangin (GAL), the bioactive component of galangal and honey, is one of the lesser‐known flavonoids but is of considerable medical interest due to its antiviral, antibacterial (Cushnie et al, 2003), and anticancer activities. Recent reviews (Rampogu et al, 2022; Singh et al, 2021; Singh et al, 2022) demonstrate that galangal is a promising anticancer agent based on its effects on numerous cancers (e.g., breast, ovarian, colon, renal, laryngeal, and cervical) and their targets.…”
Section: Covid‐19 and Medicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Galangin (GAL), the bioactive component of galangal and honey, is one of the lesser‐known flavonoids but is of considerable medical interest due to its antiviral, antibacterial (Cushnie et al, 2003), and anticancer activities. Recent reviews (Rampogu et al, 2022; Singh et al, 2021; Singh et al, 2022) demonstrate that galangal is a promising anticancer agent based on its effects on numerous cancers (e.g., breast, ovarian, colon, renal, laryngeal, and cervical) and their targets.…”
Section: Covid‐19 and Medicationmentioning
confidence: 99%
“…In 2021, Singh et al compiled a review of studies that investigated the therapeutic potential of bioactive compounds from marine sources against COVID‐19. Prior to that time, no significant information regarding flavonoids from marine vegetation had been published (Shen & Yin, 2021).…”
Section: Marine Plant Flavonoids In Covid‐19 Diseasementioning
confidence: 99%
“…Galactans extracted from Agardhiella tenera , Schizymenia binderi , and Callophyllis variegate exhibited antiviral activity by blocking the viral adhesion and replication into host cells (Ohta et al 2009 ). Carrageenan, a sulfated polysaccharide found in marine red seaweeds, has the ability to inhibit viral infections mainly by obstructing the entry of viral particles into the host cells (Singh et al 2021 ). Another study has reported that the carrageenan nasal spray was effective against the common cold caused by a human coronavirus (Koenighofer et al 2014 ).…”
Section: Marine-derived Bioactive Compounds For the Treatment Of Covi...mentioning
confidence: 99%
“…Fucoxanthin, a natural carotenoid present in brown algae, has the ability to scavenge free radicals due to the presence of a specific allenic bond in its structure. Furthermore, studies reported that fucoxanthin extracted from Sargassum siliquastrum inhibited oxidative DNA damage by increasing the production of glutathione peroxidase (Singh et al 2021 ).…”
Section: Marine-derived Bioactive Compounds For the Treatment Of Covi...mentioning
confidence: 99%
“…2 From last two decades, medicinal potential of marine sponge and algae were reported extensively; however, the story of marine NPs is very old. 7 The Cryptotethya crypta, commonly known as Caribbean sponge, was the first marine organism to be investigated and reported in detail in 1940s. 8 Spongothymidine and spongouridine are two successful antiviral drugs isolated from Caribbean sponge which later on used to develop cytosine arabinoside as an anti-cancer agents.…”
Section: Introductionmentioning
confidence: 99%